2019
DOI: 10.1186/s12889-019-6653-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between intake of red and processed meat and the risk of heart failure: a meta-analysis

Abstract: Background Many studies have assessed the association between consumption of red and processed meat and the risk of heart failure, but the results are not consistent. This meta-analysis aimed to comprehensively evaluate the relationship between intake of red and processed meat and the risk of heart failure. Methods Databases of Web of Knowledge, PubMed, and Wan Fang Med Online were retrieved up to date of August 31st, 2017. Suitable publications were identified through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 32 publications
(26 reference statements)
3
22
0
Order By: Relevance
“…The widespread popularity of high-protein diets has drawn controversy as well as scientific interest [6]. Many meta-analyses have shown a potential CVD benefit for mainly secondary prevention with increased fish intake [7] and decreased red/processed meat intake [8]. Data about the intake of legumes are less consistent but go in the same direction [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The widespread popularity of high-protein diets has drawn controversy as well as scientific interest [6]. Many meta-analyses have shown a potential CVD benefit for mainly secondary prevention with increased fish intake [7] and decreased red/processed meat intake [8]. Data about the intake of legumes are less consistent but go in the same direction [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive consumption of meat and animal products may be deleterious to human health (with meta-analytic evidence regarding cancer [1][2][3][4], cardiovascular disease [5][6][7], metabolic disease [8][9][10], obesity [11], stroke [12], and all-cause mortality [13], albeit sometimes subject to methodological limitations), promotes the emergence and spread of antibiotic-resistant pathogens [14], is a major source of greenhouse gas emissions and environmental degradation [15], and contributes to market demand for industry practices that cause the preventable suffering of more than one billion animals in the USA annually [16]. Therefore, developing simple, effective interventions to reduce meat consumption could carry widespread societal benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 Diabetes Mellitus: Several studies have reported an association between unprocessed and processed red meat and increased incidence of T2DM [36][37][38][39][40], with some reviews and meta-analyses reporting a high quality of evidence [74][75][76], with the exception of a major review and meta-analysis of cohort studies, which found a poor association between red meat consumption and the incidence of T2DM, probably due to the poor quality of included studies [77]. The new onset of T2DM appears to be multifactorial and among the various factors are, the saturated fatty acids, sodium, advanced glycation end products (AGEs), nitrates/nitrites, heme iron, branched chain aminoacids, (BCAAs), endocrine disruptor chemicals (EDCs), and the trimethylamine N-oxide (TMAO) derived from the conversion of choline in the gut [78][79][80].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, consumption of unprocessed red meat was not associated with an increased risk of HF. The study by Cui et al [36], is a review and meta-analysis of 6 studies involving 134,863 subjects ages 35-83 years, on the effects of red meat consumption on the incidence of HF. After a mean follow-up of 8.2-21.5 years, a significant association with the incidence of HF was found between the highest vs the lowest consumption of processed meat, RR 1.33 (95% CI 1.15-1.54) for the European subjects, but not for the American subjects.…”
Section: Studies Showing a Positive Association Of Red Meat Consumptimentioning
confidence: 99%